Efficacy of Herbicide Active Ingredients Against Aquatic Weeds - Stephen F. Enloe; Michael D. Netherland; William T. Haller; Kenneth Langeland (EDIS)
Weed control is often a critical component of aquatic vegetation management in Florida waters. While physical, mechanical, and biological controls are utilized where they are feasible, herbicides are the primary tool used to control many troublesome species. This document answers some common questions and provides efficacy information for all herbicide active ingredients labeled for aquatic use in Florida. Written by S. F. Enloe, M. D. Netherland, W. Haller, and K. Langeland, and published by the UF/IFAS Agronomy Department, revised February 2018. http://edis.ifas.ufl.edu/ag262